Changes in Central Macular Thickness following Single Session Multispot Panretinal Photocoagulation - Nawat Watanachai; Janejit Choovuthayakorn; Direk Patikulsila; Nimitr Ittipunkul (Journal of Ophthalmology)
Purpose. To determine changes in central subfield (CSF) macular thickness and best corrected visual acuity (BCVA) following single session, multispot panretinal photocoagulation (PRP). Methods. Forty eyes of 33 patients with newly diagnosed proliferative diabetic retinopathy were treated with single session, 20-millisecond, multispot PRP. Changes in central macular thickness and BCVA at 4- and 12-week follow-up were compared to baseline measurements. Results. Each eye received a mean (SD) of 2,750 (686.7) laser spots. At 4-week follow-up, there was a statistically significant 24.0 μm increase in mean CSF thickness (P=0.001), with a 17.4 μm increase from baseline at 12-week follow-up (P=0.002). Mean logMAR BCVA increased by 0.05 logMAR units (P=0.03) at 4-week follow-up. At 12-week follow-up, BCVA had almost returned to normal with only an increase of 0.02 logMAR units compared to baseline (P=0.39). Macular edema occurred in 2 eyes (5%) at 12-week follow-up. Conclusions. Macular thickening occurs following single session, 20-millisecond, multispot PRP, with a corresponding, mild change in BCVA. However, the incidence of macular edema appears to be low in these patients. Single session, 20-millisecond, multispot PRP appears to be a safe treatment for patients with proliferative diabetic retinopathy.